The Opportunities And Challenges Of Offshore High Schools In China - A Case Study Of Maple Leaf Educational Systems - Wang, Xiaolong (2017)
The aim of this qualitative case study of Maple Leaf Educational Systems is to explore the opportunities and challenges of offshore high schools in China from the perspectives of the State, students’ parents, schoolteachers and school leaders. Globalization, neoliberal reforms and contemporary human capital theories encourage the privatization and internationalization of education. As one of the types of international education, offshore high schools are highlighted owing to its innovation in educational models. Comparing the rising trend of offshore high schools worldwide, there is a large research gap in the field of offshore high schools.